Effect of FR194738, a potent inhibitor of squalene epoxidase, on cholesterol metabolism in HepG2 cells - Sawada, Masae; Matsuo, Masahiko; Hagihara, Hiroyuki; Tenda, Noriko; Nagayoshi, Akira; Okumura, Hiroyuki; Washizuka, Ken-ichi; Seki, Jiro; Goto, Toshio (European journal of pharmacology, 2001)
( E)- N-ethyl- N-(6,6-dimethyl-2-hepten-4-ynyl)-3-[2-methyl-2-(3-thienylmethoxy)propyloxy]benzylamine hydrochloride (FR194738) inhibited squalene epoxidase activity in HepG2 cell homogenates with an IC 50 value of 9.8 nM. In the study using intact HepG2 cells, FR194738 inhibited cholesterol synthesis from [ 14C]acetate with an IC 50 value of 4.9 nM, and induced intracellular [ 14C]squalene accumulation. On the other hand, the 3-hydroxy-3-methylglutaryl (HMG)-CoA reductase inhibitor simvastatin reduced both cholesterol and squalene synthesis from [ 14C]acetate. Incubation with simvastatin for 18 h produced increases in HMG-CoA reductase activity in HepG2 cells, which was related to the degree of reduction in cholesterol synthesis. The HMG-CoA reductase activity increased by 13- and 19-fold at the concentrations of simvastatin that inhibited cholesterol synthesis by 65% and 82%, respectively. In contrast, FR194738 did not increase HMG-CoA reductase activity at the concentrations that inhibited cholesterol synthesis by 24% and 69%, and moderate increase (4.6-fold) was observed at the concentration that inhibited cholesterol synthesis by 90%. These results suggest that non-sterol metabolite(s) derived from mevalonate prior to the squalene epoxidation step in the cholesterol synthetic cascade have a regulatory role in the suppression of HMG-CoA reductase activity. We speculate that FR194738 inhibits cholesterol synthesis with a minimal change of the regulator(s) and would be highly effective in the treatment of hypercholesterolemia.